KESEHATAN SEKOLAH, SUMBER DAYA MANUSIA, PRESTASI AKADEMIK, DAN KEEFEKTIFAN SMP STANDAR NASIONAL - Kasmadi Imam Supardi (Universitas Negeri Malang, 2012)
Abstract: School Health, Human Resources, Scholastic Achievement, and Effectiveness of National Standard Junior High Schools. The study explores the effects of school health, human resources, and scholastic achievement of students on the effectiveness of the national standard Junior High schools in Semarang. The population includes all teachers from fifteen junior high schools in Semarang categorized as national standard, while a representative sample is taken randomly from a population in each school. Data of the health of school and the education staff are collected from perception of respondents in Semarang through questionnaires, while data of the scholastic achievement is collected from the document of the national exam scores. The data are analyzed using second order confirmatory factor analysis from linear structure relationship statistical program (LISREL). The result of the study shows that the total influence of the human resources and the school health on the scholastic achievement of students is 63.81%. The scholastic achievement of the national standard schools is good for all lessons, including mathematics and natural sciences. Abstrak: Kesehatan Sekolah, Sumber Daya Manusia, Prestasi Akademik, dan Keefektifan SMP Standar Nasional. Tujuan penelitian ini adalah untuk mengungkap pengaruh kesehatan sekolah, sumber daya manusia, dan prestasi akademik bagi keefektifan sekolah standar nasional negeri di kota Semarang. Populasi penelitian ini lima belas SMP Negeri Standar Nasional di kota Semarang dengan seluruh gurunya, sedangkan sampel secara acak diambil 30% dari populasi guru yang mewakili tiap-tiap sekolah. Kesehatan sekolah dan sumber daya manusia menurut persepsi guru SMP Negeri Standar Nasional di Kota Semarang diungkap dengan angket. Sementara, prestasi akademik diungkap dari dokumen nilai ujian nasional tahun terakhir. Analisis data dilakukan dengan teknik confirmatory factor analysis second order dari program statistik linear structure relationship (LISREL). Hasil penelitian menunjukkan bahwa pengaruh sumber daya manusia dan kesehatan sekolah secara bersama-sama terhadap prestasi akademik adalah 63,81%. Prestasi akademik rata-rata nilai ujian nasional siswa SMP Negeri Standar Nasional dalam kategori baik untuk empat mata pelajaran termasuk Matematika dan IPA.